Blood transcriptional response to treatment-resistant depression during electroconvulsive therapy. (September 2021) - Israel-Elgali, Ifat; Hertzberg, Libi; Shapira, Guy; Segev, Aviv; Krieger, Israel; Nitzan, Uri; Bloch, Yuval; Pillar, Nir; Mayer, Ori; Weizman, Abraham; Gurwitz, David; Shomron, Noam
Abstract: Selective serotonin reuptake inhibitors (SSRIs) are currently the first-line antidepressant drug treatment for major depressive disorder (MDD). Treatment-resistant depression (TRD), defined as failure to achieve remission despite adequate treatment, affects 30% of persons with MDD. The current recommended treatment for TRD is electroconvulsive therapy (ECT), while ketamine is an experimentally suggested treatment. This study aimed to elucidate the transcriptional differences in peripheral blood mononuclear cells (PBMC) between individuals with TRD and a control group without a psychiatric illness; and between patients with TRD, treated with either standard antidepressant drugs alone, or in combination with ECT or ketamine. Additionally, PBMC transcriptomics were compared between treatment responders, following completion of their treatment protocols. Total RNA was extracted from PBMC of the TRD group at two time points, and RNA and miRNA expression were profiled. Multiple mRNAs and miRNAs were found to be modified, with two protein coding genes, FKBP5 and ITGA2B, which are up- and downregulated, respectively; and several miRNAs have shown changes following successful ECT treatment. Further analysis demonstrated the direct functional regulation of ITGA2B by miR-24–3p. Our findings suggest that PBMC expression levels of FKBP5, ITGA2B, and miR-24–3p should be further explored as tentative ECT response biomarkers.